Generalized Gudermannian function - Neuman, Edward (Issues of analysis, 2018)
Wilker and Huygens-type inequalities involving generalized Gudermannian function and its inverse function are established. These results are obtained with the aid of the p-version of the Schwab-Borchardt mean. Generalized one-parameter trigonometric and hyperbolic functions play a crucial role in this paper.